‘I don’t like K-pop, only JYJ-pop’: Disenchanted Pop Cosmopolitans in Transnational K-pop Online Fandom - Elan Lazuardi (Sasdaya: Gadjah Mada Journal of Humanities, 2026)
K-pop has gained considerable traction not only throughout East and Southeast Asia but also across European and American fandom, thereby integrating these audiences into what Henry Jenkins describes as “pop cosmopolitanism”. Based on an online ethnographic study conducted in 2012 involving fourteen fans who regularly participated in JYJ3, a fan-operated website dedicated to the K-pop group JYJ, this paper investigates how fans construct their identities as part of a transnational modern community while simultaneously cultivating moral discernment. Drawing on Hannerz’s concept of “cosmopolitan” and Jenkins’s notion of “pop cosmopolitan,” the analysis demonstrates how transnational fans leverage their exposure to diverse cultural and social contexts in their processes of self-fashioning, both culturally and morally. The findings indicate that fans’ engagement with JYJ transcends mere aesthetics or eclectic preferences. Instead, their attachment is influenced by a reflexive awareness of the industry’s “manufacturedness,” JYJ’s role as underdogs, and the moral and emotional responsibilities fans perceive toward the group. Through participation in JYJ3, fans negotiate the significance of caring for, protecting, or distancing themselves from idols and fandom, with these negotiations becoming central to their self-understanding as cosmopolitan subjects. These negotiations become central to how they understand themselves as cosmopolitan subjects. This study suggests that global pop culture fandom – within K-pop and beyond – is increasingly driven by moral work. It advocates for expanding analyses of pop cosmopolitanism to encompass the nuanced moral work through which fans navigate evolving expectations of care and responsibility within networked fan cultures.